Banjir, Kapankan Berakhir? - Mardiyono, Mardiyono (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
The rain in Indonesia ussualy become headline in media. Usually, rain cause of flood. When floods end? Why is the forest devilotery happen? What are the government action to stop this?. In fact, there are big interferences of local government on processing forest problem. Government intervence only conducted by passing PT Perhutani showed by government in managing forest in Madura and Java. Operation legality of PT Perhutani with government regulation No. 53 year 1999 and government regulation No. 14 year 2001, about the change of transformation of public company foresty become Coparthenship company or PT Perhutani (Coparthenship)In this paper, the writer will give recommendation over how important the local government to more active on observation, management, and forest benefit with local regulation about forest protection in that location. With making observation and reins to the program, act and forest from PT Perhutani. Government should give education to society about the important to keep environmental health and leave mental attitude which is not praised like throw waste or rubbish in the river, and give more responsibility to protect the forest to society of forest countryside.Key words: Flood, Society, Government, Responsibility